Ḥadīts sebagai Prasyarat Akurasi Penafsiran al-Qur’ān Tekstual - Abdullah Karim (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2012)
This article shows that the accuracy of using Ḥadīth, as a tool to interpret the Qur’ān, is really helpful in interpreting the Qur’ān intextual way. The application of Ḥadīth, as an interpreter, should be used in proportional, professional, and contextual manners. Through studying the Ḥadīth by those three prerequisites, this writing simultaneously enforces an opinion stating that the Qur’ānic interpretation through bi-al-ma’tsūr is the best one, rather than through bi-al-ra’y.DOI: 10.15408/ref.v13i3.908